2003
DOI: 10.1016/s0002-9270(03)00750-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial determinants of relapse in ulcerative colitis: a longitudinal study

Abstract: After controlling for demographic and clinical variables, more recent stressful events were associated with earlier time to relapse. These findings, which support a biopsychosocial model of disease, might help clinicians identify patients who might benefit from more intensive maintenance medical therapy and behavioral medicine interventions to reduce stress and improve coping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(106 citation statements)
references
References 0 publications
3
99
0
4
Order By: Relevance
“…Thus, studies that are not cohesively designed can lead to confusing results. In UC, Bitton et al 28 reported that the odds ratio of relapse by life events was not very high (1.26 per event). Levenstein et al 27 demonstrated a failure to determine a relationship between life events and relapse.…”
Section: Psychological Stress In the Course Of Human Ibdmentioning
confidence: 99%
“…Thus, studies that are not cohesively designed can lead to confusing results. In UC, Bitton et al 28 reported that the odds ratio of relapse by life events was not very high (1.26 per event). Levenstein et al 27 demonstrated a failure to determine a relationship between life events and relapse.…”
Section: Psychological Stress In the Course Of Human Ibdmentioning
confidence: 99%
“…It is also recognized that individuals with IBD who are experiencing symptoms are more likely to have higher levels of perceived stress (8)(9)(10). Perceived stress, which takes into account the perceived controllability, manageability, and personal impact of situations, has a strong and consistent association with concurrent and subsequent IBD symptoms ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bitton et al followed 60 patients with clinically and endoscopically inactive ulcerative colitis prospectively for one year and discovered that the number of important life events was significantly higher in the period preceding exacerbation [1]. Duffy et al have also shown there is a positive temporal association between stress and exacerbation of IBD.…”
Section: Introductionmentioning
confidence: 99%